Rain-erosion-resistant ceramic-based composite material as well as preparation method and application thereof
By depositing the BN interface layer on the surface of the fiber prefabricated body of the ceramic matrix composite material and introducing SiOC-Si3N4 reinforced matrix, the problem of existing ceramic matrix composite materials being prone to cracking or falling off in rain etching environments is solved, and the efficient rain resistance of the material is achieved Improved corrosion, mechanical and electromagnetic properties.
Patent Information
- Application Number
- CN202411542347.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-14
AI Technical Summary
Existing ceramic matrix composite materials are prone to cracking or falling off in rain-etching environments, and their mechanical properties, electromagnetic properties and rain-etching resistance are insufficient.
A BN interface layer is deposited on the surface or inside of the fiber preform by chemical vapor permeation, and a SiOC-Si3N4 reinforcement matrix is introduced into the fiber preform with a BN interface layer to form a rain-resistant ceramic matrix composite material.
The corrosion resistance, mechanical properties and electromagnetic properties of ceramic matrix composites are improved, and the preparation method is simple and the period is short.
Smart Images

Figure CN119430956A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of load-bearing and wave-absorbing ceramic-based composite materials, and in particular relates to a rain-erosion-resistant ceramic-based composite material and a preparation method and application thereof. Background Art
[0002] The coastal areas are in a rainy environment. When an aircraft passes through a rainy area at high speed, it is very easy for the high-speed impact of raindrops to cause cracks, corrosion pits, and even serious damage and deformation on the surface of the structure, resulting in reduced structural strength of the components and affecting the core functions of the aircraft.
[0003] Ceramic matrix composites are light, high temperature resistant, anti-oxidation, corrosion resistant, excellent mechanical properties, and highly designable electromagnetic properties. They are key candidate materials for aircraft hot end components. Currently, the commonly used high temperature resistant load-bearing and absorbing integrated ceramic matrix composites are SiC fiber and Al2O3 fiber reinforced ceramic matrix composites. In composite materials, the interface bonding strength between the fiber and the matrix has an important influence on the overall performance of the material. The prior art discloses an inorganic anti-rain erosion coating on the surface of a quartz fiber reinforced quartz-based composite material and a preparation method thereof. The method is to coat a high-density, uniform and smooth inorganic anti-rain erosion coating on the surface of a quartz fiber reinforced quartz-based composite material, and optimize the anti-rain erosion and thermal shock stability of the inorganic coating on the surface of the composite material by regulating the formula of the inorganic powder, but the inorganic coating is prone to cracking or falling off in a long-term extreme rain erosion environment; the prior art also discloses a corrosion-resistant ceramic-based composite material and a preparation method thereof, the raw material of the ceramic-based composite material includes aramid fiber, because aramid has adhesion and good flexibility, the fiber can be tightly combined in the matrix, and the flexibility of the material is increased, and aramid is a corrosion-resistant material, and the addition of aramid can improve the anti-rain erosion ability of the material, but the raw material aramid fiber is high in price and poor in electromagnetic properties, which limits the wide application of the ceramic-based composite material. Therefore, it is particularly important to develop a ceramic-based composite material that can resist rain erosion and has excellent mechanical properties and electromagnetic properties. Summary of the invention
[0004] In view of the above-mentioned prior art, the present invention discloses an anti-rain erosion ceramic-based composite material and a preparation method and application thereof, so as to solve the technical problems of poor mechanical properties, electromagnetic properties and anti-rain erosion properties of the ceramic-based composite material in the prior art.
[0005] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is: to provide an anti-rain erosion ceramic-based composite material and a preparation method thereof, the preparation method comprising the following steps: firstly, a BN interface layer is deposited on the surface or in the internal voids of a fiber preform by chemical vapor infiltration to obtain a fiber preform having a BN interface layer; and then a reinforcing matrix is introduced into the fiber preform having the BN interface layer to obtain; the reinforcing matrix is SiOC-Si3N4.
[0006] Based on the above technical solution, the present invention can also be improved as follows.
[0007] Furthermore, the fiber preform is an Al2O3 fiber preform or a SiC fiber preform.
[0008] Furthermore, the preparation method of the fiber preform includes the following steps: heat treating Al2O3 fiber cloth or SiC fiber cloth, stacking and fixing to obtain the Al2O3 fiber preform or SiC fiber preform; the heat treatment temperature is 500-600°C, the heat treatment time is 2-3h; the stacking thickness is 3-4mm.
[0009] Furthermore, in the chemical vapor infiltration method, the precursor is a BCl3-NH3-H2-Ar system, the deposition temperature is 650-670°C, the deposition time is 40-50h; and the thickness of the BN interface layer is 250-500nm.
[0010] Furthermore, the preparation of introducing SiOC-Si3N4 into an Al2O3 fiber preform with a BN interface layer includes the following steps: firstly, a Si3N4 matrix is prepared in the Al2O3 fiber preform with a BN interface layer by chemical vapor infiltration to obtain an Al2O3 fiber / Si3N4 composite material, the Al2O3 fiber / Si3N4 composite material is impregnated with an impregnation liquid under vacuum conditions, and then a cracking reaction is carried out under inert gas conditions, and the Al2O3 fiber / SiOC-Si3N4 composite material is obtained after repeated impregnation and cracking reactions for 5 to 8 times; when preparing the Si3N4 matrix, the precursor in the chemical vapor infiltration method is SiCl4-NH3-H2-Ar, the deposition temperature is 800 to 820°C, and the deposition time is 300 to 500 hours.
[0011] Furthermore, the preparation of introducing SiOC-Si3N4 into a SiC fiber preform with a BN interface layer includes the following steps: first, the SiC fiber preform with a BN interface layer is impregnated with an impregnation liquid under vacuum conditions, and then a cracking reaction is carried out under inert gas conditions, and the SiC fiber / SiOC composite material is obtained after repeated impregnation and cracking reactions for 5 to 8 times, and then a Si3N4 matrix is prepared in the SiC fiber / SiOC composite material by chemical vapor infiltration to obtain a SiC fiber / SiOC-Si3N4 composite material, and when preparing the Si3N4 matrix, the precursor in the chemical vapor infiltration method is SiCl4-NH3-H2-Ar, the deposition temperature is 800 to 820°C, and the deposition time is 300 to 500 hours.
[0012] Furthermore, the immersion vacuum is -0.5 to -0.1 MPa; the immersion liquid is a polysiloxane solution with a concentration of 30 to 50 wt%, and the solvent of the polysiloxane solution is xylene; the immersion time is 30 to 60 minutes; the inert gas is argon; the cracking temperature is 800 to 900° C., and the cracking time is 2 to 3 hours.
[0013] The invention also discloses the application of the rain erosion resistant ceramic matrix composite material in the preparation of the hot end components of an aircraft.
[0014] The beneficial effects of the present invention are:
[0015] 1. The molding method of the anti-rain erosion ceramic-based composite material in the present invention is simple and the preparation cycle is short. The present invention uses Al2O3 fiber or SiC fiber as raw material and combines chemical vapor infiltration process and polymer impregnation and cracking process to prepare the ceramic-based composite material. The obtained ceramic-based composite material has good wave absorption performance, mechanical properties and anti-rain erosion performance.
[0016] 2. In the preparation method of the present invention, a fiber preform with a BN interface layer is first obtained by a chemical vapor infiltration process. The BN interface layer has good thermal stability and chemical stability and can serve as a transition layer between the fiber and the reinforcing matrix. Then, for different fiber preforms, the order of the chemical vapor infiltration process and the polymer impregnation and cracking process is regulated to form a uniform and continuous reinforcing matrix on the fiber surface to make the fiber evenly loaded. The synergistic effect between the BN interface layer, the reinforcing matrix and the fiber improves the mechanical properties and rain erosion resistance of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 is a SEM image of the SiC fiber / SiOC-Si3N4 composite material prepared in Example 1;
[0018] Figure 2 is a SEM image of the SiC fiber / Si3N4 composite material prepared in Comparative Example 1;
[0019] Figure 3 This is a SEM image of the BN interface layer in the SiC fiber / SiOC-Si3N4 composite material prepared in Example 1;
[0020] Figure 4 This is a SEM image of the BN interface layer in the SiC fiber / SiOC-Si3N4 composite material prepared in Example 5;
[0021] Figure 5 The optical microscope reconstruction images of the SiC fiber / SiOC-Si3N4 composite material prepared in Example 1 after being impacted for different times;
[0022] Figure 6This is a graph showing the electromagnetic performance test results of the SiC fiber / SiOC-Si3N4 composite material prepared in Example 1;
[0023] Figure 7 This is a graph showing the electromagnetic performance test results of the SiC fiber / SiOC-Si3N4 composite material prepared in Example 1 after being impacted by water drops for different times;
[0024] Figure 8 This is a graph showing the electromagnetic performance test results of the SiC fiber / Si3N4 composite material prepared in Comparative Example 1;
[0025] Fig. 9 This is a graph showing the electromagnetic performance test results of the SiC fiber / Si3N4 composite material prepared in Comparative Example 1 after being impacted by water drops for different times. DETAILED DESCRIPTION
[0026] The specific implementation modes of the present invention are described in detail below with reference to the embodiments.
[0027] Example 1
[0028] A rain erosion resistant ceramic matrix composite material, the preparation method of which comprises the following steps:
[0029] S1: The SiC fiber cloth is cut into a size of 20 cm×20 cm, and then the cut fiber cloth is placed in a box furnace and heat-treated at 550° C. for 2.5 h to remove the sizing agent on the fiber surface, and then the heat-treated SiC fiber cloth is stacked to a thickness of 3 mm, and then the stacked SiC fiber cloth is fixed with a graphite grinder to obtain a SiC fiber preform;
[0030] S2: The BN interface layer is deposited in the SiC fiber preform by chemical vapor infiltration. The precursor in the chemical vapor infiltration method is BCl3-NH3-H2-Ar system. The deposition temperature is 670℃, the deposition time is 40h, and the thickness of the BN interface layer is 295nm.
[0031] S3: Under the condition of a vacuum degree of -0.1MPa, the SiC fiber preform with a BN interface layer is immersed in a polysiloxane solution with a concentration of 50wt% for 30min, the solvent of the polysiloxane solution is xylene, and the impregnated SiC fiber preform with a BN interface layer is subjected to a cracking reaction at 800℃ in an Ar atmosphere for 2.5h. After repeated impregnation and cracking reactions for 5 times, a SiC fiber / SiOC composite material is obtained; a Si3N4 matrix is prepared in the SiC fiber / SiOC composite material by chemical vapor infiltration to obtain a SiC fiber / SiOC-Si3N4 composite material, the precursor in the chemical vapor infiltration method is SiCl4-NH3-H2-Ar, the deposition temperature is 800℃, and the deposition time is 300h.
[0032] Example 2
[0033] A rain erosion resistant ceramic matrix composite material, the preparation method of which comprises the following steps:
[0034] S1: Cut the Al2O3 fiber cloth into a size of 20 cm×20 cm, then put the cut fiber cloth into a box furnace, and heat treat it at 550° C. for 2.5 hours to remove the sizing agent on the fiber surface, then stack the heat-treated Al2O3 fiber cloth to a thickness of 3 mm, and then fix the stacked Al2O3 fiber cloth with a graphite grinder to obtain an Al2O3 fiber preform;
[0035] S2: The BN interface layer is deposited in the Al2O3 fiber preform by chemical vapor infiltration. The precursor in the chemical vapor infiltration method is BCl3-NH3-H2-Ar system. The deposition temperature is 650℃, the deposition time is 45h, and the thickness of the BN interface layer is 400nm.
[0036] S3: A Si3N4 matrix is prepared in an Al2O3 fiber preform with a BN interface layer by chemical vapor infiltration to obtain an Al2O3 fiber / Si3N4 composite material, wherein the precursor in the chemical vapor infiltration method is SiCl4-NH3-H2-Ar, the deposition temperature is 800°C, and the deposition time is 400h; then, under a vacuum degree of -0.1MPa, the Al2O3 fiber / Si3N4 composite material is immersed in a 50wt% polysiloxane solution for 30min, the solvent of the polysiloxane solution is xylene, and the immersed Al2O3 fiber / Si3N4 composite material is subjected to a cracking reaction at 800°C in an Ar atmosphere for 2.5h, and the Al2O3 fiber / SiOC-Si3N4 composite material is obtained after repeated impregnation and cracking reactions for 6 times.
[0037] Example 3
[0038] A rain erosion resistant ceramic matrix composite material, the preparation method of which comprises the following steps:
[0039] S1: Cut the Al2O3 fiber cloth into a size of 20 cm×20 cm, then put the cut fiber cloth into a box furnace, and heat treat it at 500° C. for 3 hours to remove the sizing agent on the fiber surface, then stack the heat-treated Al2O3 fiber cloth to a thickness of 4 mm, and then use a graphite grinder to fix the stacked Al2O3 fiber cloth to obtain an Al2O3 fiber preform;
[0040] S2: The BN interface layer is deposited in the Al2O3 fiber preform by chemical vapor infiltration. The precursor in the chemical vapor infiltration method is BCl3-NH3-H2-Ar system, the deposition temperature is 650℃, the deposition time is 40h, and the thickness of the BN interface layer is 300nm;
[0041] S3: A Si3N4 matrix is prepared in an Al2O3 fiber preform with a BN interface layer by chemical vapor infiltration to obtain an Al2O3 fiber / Si3N4 composite material, wherein the precursor in the chemical vapor infiltration method is SiCl4-NH3-H2-Ar, the deposition temperature is 800°C, and the deposition time is 300h; then, under a vacuum degree of -0.5MPa, the Al2O3 fiber / Si3N4 composite material is immersed in a 30wt% polysiloxane solution for 60min, the solvent of the polysiloxane solution is xylene, and the impregnated Al2O3 fiber / Si3N4 composite material is subjected to a cracking reaction at 850°C in an Ar atmosphere for 3h, and the Al2O3 fiber / SiOC-Si3N4 composite material is obtained after repeated impregnation and cracking reactions for 5 times.
[0042] Example 4
[0043] A rain erosion resistant ceramic matrix composite material, the preparation method of which comprises the following steps:
[0044] S1: The Al2O3 fiber cloth is cut into a size of 20 cm×20 cm, and then the cut fiber cloth is placed in a box furnace and heat-treated at 600° C. for 2 h to remove the sizing agent on the fiber surface, and then the heat-treated Al2O3 fiber cloth is stacked to a thickness of 3 mm, and then the stacked Al2O3 fiber cloth is fixed with a graphite grinder to obtain an Al2O3 fiber preform;
[0045] S2: The BN interface layer is deposited in the Al2O3 fiber preform by chemical vapor infiltration. The precursor in the chemical vapor infiltration method is BCl3-NH3-H2-Ar system, the deposition temperature is 670℃, the deposition time is 50h, and the thickness of the BN interface layer is 500nm;
[0046] S3: A Si3N4 matrix is prepared in an Al2O3 fiber preform with a BN interface layer by chemical vapor infiltration to obtain an Al2O3 fiber / Si3N4 composite material, wherein the precursor in the chemical vapor infiltration method is SiCl4-NH3-H2-Ar, the deposition temperature is 820°C, and the deposition time is 500h; then, under a vacuum degree of -0.1MPa, the Al2O3 fiber / Si3N4 composite material is immersed in a 40wt% polysiloxane solution for 50min, the solvent of the polysiloxane solution is xylene, and the impregnated Al2O3 fiber / Si3N4 composite material is subjected to a cracking reaction at 900°C in an Ar atmosphere for 2h, and the Al2O3 fiber / SiOC-Si3N4 composite material is obtained after repeated impregnation and cracking reactions for 8 times.
[0047] Example 5
[0048] A rain erosion resistant ceramic matrix composite material, the preparation method of which comprises the following steps:
[0049] S1: The SiC fiber cloth is cut into a size of 20 cm×20 cm, and then the cut fiber cloth is placed in a box furnace and heat-treated at 500° C. for 2 h to remove the sizing agent on the fiber surface, and then the heat-treated SiC fiber cloth is stacked to a thickness of 4 mm, and then a graphite grinder is used to fix the stacked SiC fiber cloth to obtain a SiC fiber preform;
[0050] S2: The BN interface layer is deposited in the SiC fiber preform by chemical vapor infiltration. The precursor in the chemical vapor infiltration method is BCl3-NH3-H2-Ar system. The deposition temperature is 650℃, the deposition time is 45h, and the thickness of the BN interface layer is 260nm.
[0051] S3: Under the condition of a vacuum degree of -0.5MPa, the SiC fiber preform with a BN interface layer is immersed in a polysiloxane solution with a concentration of 30wt% for 40min, the solvent of the polysiloxane solution is xylene, and the impregnated SiC fiber preform with a BN interface layer is subjected to a cracking reaction at 900℃ in an Ar atmosphere for 2h. After repeated impregnation and cracking reactions for 8 times, a SiC fiber / SiOC composite material is obtained; a Si3N4 matrix is prepared in the SiC fiber / SiOC composite material by chemical vapor infiltration to obtain a SiC fiber / SiOC-Si3N4 composite material, the precursor in the chemical vapor infiltration method is SiCl4-NH3-H2-Ar, the deposition temperature is 820℃, and the deposition time is 400h.
[0052] Example 6
[0053] A rain erosion resistant ceramic matrix composite material, the preparation method of which comprises the following steps:
[0054] S1: The SiC fiber cloth is cut into a size of 20 cm×20 cm, and then the cut fiber cloth is placed in a box furnace and heat-treated at 600° C. for 3 h to remove the sizing agent on the fiber surface, and then the heat-treated SiC fiber cloth is stacked to a thickness of 4 mm, and then the stacked SiC fiber cloth is fixed with a graphite grinder to obtain a SiC fiber preform;
[0055] S2: The BN interface layer is deposited in the SiC fiber preform by chemical vapor infiltration. The precursor in the chemical vapor infiltration method is BCl3-NH3-H2-Ar system, the deposition temperature is 650°C, the deposition time is 50h, and the thickness of the BN interface layer is 500nm;
[0056] S3: Under the condition of a vacuum degree of -0.1MPa, the SiC fiber preform with a BN interface layer is immersed in a polysiloxane solution with a concentration of 40wt% for 60min, the solvent of the polysiloxane solution is xylene, and the impregnated SiC fiber preform with a BN interface layer is subjected to a cracking reaction at 850°C in an Ar atmosphere for 3h. After repeated impregnation and cracking reactions for 6 times, a SiC fiber / SiOC composite material is obtained; a Si3N4 matrix is prepared in the SiC fiber / SiOC composite material by chemical vapor infiltration to obtain a SiC fiber / SiOC-Si3N4 composite material, the precursor in the chemical vapor infiltration method is SiCl4-NH3-H2-Ar, the deposition temperature is 800°C, and the deposition time is 400h.
[0057] Comparative Example 1
[0058] A ceramic matrix composite material, the preparation method of which comprises the following steps:
[0059] S1: The SiC fiber cloth is cut into a size of 20 cm×20 cm, and then the cut fiber cloth is placed in a box furnace and heat-treated at 550° C. for 2.5 h to remove the sizing agent on the fiber surface, and then the heat-treated SiC fiber cloth is stacked to a thickness of 3 mm, and then the stacked SiC fiber cloth is fixed with a graphite grinder to obtain a SiC fiber preform;
[0060] S2: The BN interface layer is deposited in the SiC fiber preform by chemical vapor infiltration. The precursor in the chemical vapor infiltration method is BCl3-NH3-H2-Ar system. The deposition temperature is 670℃, the deposition time is 40h, and the thickness of the BN interface layer is 295nm.
[0061] S3: A Si3N4 matrix was prepared in a SiC fiber preform with a BN interface layer by chemical vapor infiltration to obtain a SiC fiber / Si3N4 composite material. The precursor in the chemical vapor infiltration method was SiCl4-NH3-H2-Ar, the deposition temperature was 800°C, and the deposition time was 300 h.
[0062] Comparative Example 2
[0063] A ceramic matrix composite material, the preparation method of which comprises the following steps:
[0064] S1: Cut the Al2O3 fiber cloth into a size of 20 cm×20 cm, then put the cut fiber cloth into a box furnace, and heat treat it at 550° C. for 2.5 hours to remove the sizing agent on the fiber surface, then stack the heat-treated Al2O3 fiber cloth to a thickness of 3 mm, and then fix the stacked Al2O3 fiber cloth with a graphite grinder to obtain an Al2O3 fiber preform;
[0065] S2: The BN interface layer is deposited in the Al2O3 fiber preform by chemical vapor infiltration. The precursor in the chemical vapor infiltration method is BCl3-NH3-H2-Ar system. The deposition temperature is 650℃, the deposition time is 45h, and the thickness of the BN interface layer is 400nm.
[0066] S3: Then, under the condition of a vacuum degree of -0.1MPa, the Al2O3 fiber preform with a BN interface layer is immersed in a polysiloxane solution with a concentration of 50wt% for 30min, the solvent of the polysiloxane solution is xylene, and the impregnated Al2O3 fiber / Si3N4 composite material is subjected to a thermal cracking reaction at 800℃ in Ar atmosphere for 2.5h. After repeated impregnation and cracking reaction for 6 times, the Al2O3 fiber / SiOC composite material is obtained.
[0067] Experimental example
[0068] 1. Structural test
[0069] The microstructures of the samples prepared in Example 1, Example 5 and Comparative Example 1 were characterized by scanning electron microscopy. Figures 1 to 4 As shown, Figure 1 and Figure 2 In the figure, a, b and c correspond to electron microscope images at different magnifications. It can be seen that compared with Comparative Example 1, the sample prepared in Example 1 has fewer voids, a clear interface between the fiber preform and the reinforcing matrix, and a precise combination without obvious cracks and separation, indicating that the sample has a better structural density. Figures 3-4 It can be seen that the thickness of the BN interface layer of the sample prepared in Example 1 is 295 nm, and the thickness of the BN interface layer of the sample prepared in Example 5 is 260 nm.
[0070] 2. Performance Testing
[0071] ① Use a high-speed water droplet jet system to impact the samples prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 2, ensuring that the single droplet jet speed is 350 m / s, and use an optical microscope to observe the samples after impact and reconstruct the microstructure. The optical microscope reconstruction image of the sample after impact in Example 1 is as follows: Figure 5 As shown, a, b, c and d correspond to 4, 8, 14 and 18 times of impact respectively. The surface digital grating deformation and phase change of each sample before and after different impact times are measured by phase measurement technology, and the sample erosion depth (%) is calculated. The calculation results are shown in Table 1. It can be seen from Table 1 that the sample prepared in the embodiment has better rain erosion resistance.
[0072] Table 1
[0073]
[0074] ② The mechanical properties of the samples were tested using a universal material testing machine. The test results are shown in Table 2. It can be seen from Table 2 that the samples prepared in the embodiment have better mechanical properties.
[0075] Table 2
[0076]
[0077]
[0078] ③ Generate electromagnetic wave signals through the transmitting antenna, capture the reflected wave signals through the receiving antenna, use the vector network analyzer to reflect the wave signals, and calculate the reflection loss value (RL). Figures 6 to 9 The reflection loss 2D curve of samples with different thicknesses is an important indicator for evaluating electromagnetic wave absorption performance. Figure 6 It can be seen that the sample prepared in Example 1 exhibits efficient electromagnetic wave absorption performance, and its minimum reflection loss (RL min ) is -5.22dB, from Figure 7 It can also be seen that the reflection loss of the example sample after being impacted by different water droplets is also smaller than that of the sample prepared in comparative example 1.
[0079] Although the specific implementation of the present invention is described in detail in conjunction with the embodiments, it should not be understood as limiting the scope of protection of this patent. Within the scope described in the claims, various modifications and variations that can be made by those skilled in the art without creative work still fall within the scope of protection of this patent.
Claims
1. A method for preparing a rain erosion resistant ceramic matrix composite material, characterized in that: The following steps are involved: First, a BN interface layer is deposited on the surface or in the internal gap of a fiber preform by chemical vapor infiltration to obtain a fiber preform with a BN interface layer; then a reinforcing matrix is introduced into the fiber preform with the BN interface layer to obtain a fiber preform; the reinforcing matrix is SiOC-Si3N4.
2. The preparation method according to claim 1, characterized in that: The fiber preform is an Al2O3 fiber preform or a SiC fiber preform.
3. The preparation method according to claim 2, characterized in that: The preparation method of the fiber preform comprises the following steps: heat treating Al2O3 fiber cloth or SiC fiber cloth, stacking and fixing to obtain the Al2O3 fiber preform or SiC fiber preform; the heat treatment temperature is 500-600°C, the heat treatment time is 2-3h; the stacking thickness is 3-4mm.
4. The preparation method according to claim 3, characterized in that: The precursor in the chemical vapor infiltration method is a BCl3-NH3-H2-Ar system, the deposition temperature is 650-670°C, the deposition time is 40-50h; the thickness of the BN interface layer is 250-500nm.
5. The preparation method according to claim 4, characterized in that: The preparation of introducing the SiOC-Si3N4 into the Al2O3 fiber preform with a BN interface layer includes the following steps: firstly, a Si3N4 matrix is prepared in the Al2O3 fiber preform with the BN interface layer by a chemical vapor infiltration method to obtain an Al2O3 fiber / Si3N4 composite material, the Al2O3 fiber / Si3N4 composite material is impregnated with an impregnation liquid under vacuum conditions, and then a cracking reaction is carried out under inert gas conditions, and the Al2O3 fiber / Si3N4-SiOC composite material is obtained after repeated impregnation and cracking reactions for 5 to 8 times; when preparing the Si3N4 matrix, the precursor in the chemical vapor infiltration method is SiCl4-NH3-H2-Ar, the deposition temperature is 800 to 820°C, and the deposition time is 300 to 500 hours.
6. The preparation method according to claim 4, characterized in that: The preparation of introducing the SiOC-Si3N4 into the SiC fiber preform with a BN interface layer includes the following steps: first, the SiC fiber preform with a BN interface layer is impregnated with an impregnation liquid under vacuum conditions, and then a cracking reaction is carried out under inert gas conditions, and the SiC fiber / SiOC composite material is obtained after repeated impregnation and cracking reactions for 5 to 8 times, and then a Si3N4 matrix is prepared in the SiC fiber / SiOC composite material by chemical vapor infiltration to obtain a SiC fiber / SiOC-Si3N4 composite material, wherein the precursor in the chemical vapor infiltration method when preparing the Si3N4 matrix is SiCl4-NH3-H2-Ar, the deposition temperature is 800 to 820°C, and the deposition time is 300 to 500 hours.
7. The preparation method according to claim 5 or 6, characterized in that: The immersion vacuum is -0.5 to -0.1 MPa; the immersion liquid is a polysiloxane solution with a concentration of 30 to 50 wt%, and the solvent of the polysiloxane solution is xylene; the immersion time is 30 to 60 minutes; the inert gas is argon; the cracking temperature is 800 to 900° C., and the cracking time is 2 to 3 hours.
8. A ceramic matrix composite material, characterized in that: The anti-rain erosion ceramic-based composite material is prepared by the preparation method of any one of claims 1 to 7.
9. An application of a rain erosion resistant ceramic matrix composite material, characterized in that: The rain erosion resistant ceramic matrix composite material according to claim 8 is used to prepare hot end components of aircraft.
Citation Information
Patent Citations
Preparation method of wave-transparent fiber toughened boron nitride ceramic based wave-transparent composite material
CN103265303A
High-temperature broadband wave-absorbing Al2O3f reinforced ceramic-based composite material and integrated preparation method
CN114149272A
SiC / Si3N4 compound with electromagnetic wave absorption performance and preparation method thereof
CN115417685A
Preparation method of stealth structure type oxide fiber reinforced silicon-based ceramic composite material
CN118063227A
Ceramic matrix composites
EP1004559A2
Cited By
Structural wave-absorbing integrated ceramic-based composite material prepared based on 3D printing and preparation method of structural wave-absorbing integrated ceramic-based composite material
CN121202577A